ADEQUACY OF FINE NEEDLE ASPIRATION CYTOLOGY FOR CONFIRMATION OF TYPE OF THYROID LESIONS - ASHFAQ , F; ZAHID , MM; AHMAD , K; AHMED , R; ALI , I; MEHMOOD , S (Biological and Clinical Sciences Research Journal, 2023)
Thyroid nodules commonly arise within an otherwise normal thyroid gland. Nodular thyroid lesions are so common that they are present as solitary or multiple nodules. Fine-needle aspiration and capillary sampling are the 2 most commonly used diagnostic techniques for assessing cytopathology of thyroid nodules. Objectives: To determine the frequency of adequacy of fine needle aspiration cytology for detecting thyroid lesions in patients with thyroid lesions. Materials and Methods: 75 patients with thyroid lesions were enrolled after meeting the inclusion criteria. Informed consent and demographic information were taken. The patient’s TSH level was noted. Then, FNAC was done after collecting the specimen through FNAC, and the specimen was sent to the hospital laboratory for cytology. The diagnosis was made. All the collected information was noted and entered in SPSS version 20 for analysis. Results: In our study, the mean age of the patients was 43.20±9.35 years, male to female ratio of the patients was 0.7:1. Out of 75 patients on FNAC, 50(66.7%) samples were adequate. In this study, a malignant thyroid nodule on FNAC was noted in 21(28%) patients, and a benign thyroid nodule on FNAC was noted in 54(72%) patients. Conclusion: The adequacy of fine needle aspiration cytology for detecting thyroid lesions in patients with thyroid lesions was 66.7%.